MiR-23a induced the activation of CDC42/PAK1 pathway and cell cycle arrest in human cov434 cells by targeting FGD4 - Ji Lin; Huijuan Huang; Liheng Lin; Weiwei Li; Jianfen Huang (BMC, 2020)
Abstract Background MiRNAs play important roles in the development of ovarian cancer, activation of primitive follicles, follicular development, oocyte maturation and ovulation. In the present study, we investigated the specific role of miR-23a in cov434 cells. Results Downregulation of miR-23a was observed in serum of PCOS patients compared with the healthy control, suggesting the inhibitory effect of miR-23a in PCOS. MiR-23a was positively correlated with Body Mass Index (BMI) and negatively correlated with Luteinizing hormone (LH), Testostrone (T), Glucose (Glu) and Insulin (INS) of PCOS patients. MiR-23a mimic inhibited the proliferation and promoted apoptosis of human cov434 cells. In addition, flow cytometry assay confirmed that miR-23a blocked cell cycle on G0/G1 phase. MiR-23a inhibitor showed opposite results. Furthermore, double luciferase reporter assay proved that miR-23a could bind to the 3'UTR of FGD4 directly through sites predicted on Target Scan. FGD4 level was significantly suppressed by miR-23a mimic, but was significantly enhanced by miR-23a inhibitor. We further proved that miR-23a increased the expression of activated CDC42 (GTP bround) and p-PAK-1, suggesting that miR-23a induced cell cycle arrest through CDC42/PAK1 pathway. Conclusions In conclusion, our study reveals that miR-23a participates in the regulation of proliferation and apoptosis of cov434 cells through target FGD4, and may play a role in the pathophysiology of PCOS.